1961
DOI: 10.2118/1566-g-pa
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gas Hydrates at Pressures to 10,000 psia

Abstract: This paper presents the results of the data obtained in the first stage of a long-range study at high pressures of the system, vapor-hydrate-water rich liquid-hydrocarbon rich liquid. The data presented are for the three-phase systems in which no hydrocarbon liquid exists. Tests were performed on 10 gases at pressures from 1,000 to 10,000 psia. One of these was substantially pure methane, and the remainder were binary mixtures of methane with ethane, propane, iso-butane and normal butane. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(50 citation statements)
references
References 0 publications
6
44
0
Order By: Relevance
“…(2), the three-phase equilibrium pressures increase monotonically as temperature increases. Under the present experimental condition, the three-phase equilibrium curves of CH 4 + C 2 H 6 mixed-gas hydrate would not intersect that of pure CH 4 hydrate, opposed to the previous data [14]. The structural transition points obtained in the present study agree with those reported by Subramanian, Kini, Dec and Sloan [1].…”
Section: Resultssupporting
confidence: 71%
“…(2), the three-phase equilibrium pressures increase monotonically as temperature increases. Under the present experimental condition, the three-phase equilibrium curves of CH 4 + C 2 H 6 mixed-gas hydrate would not intersect that of pure CH 4 hydrate, opposed to the previous data [14]. The structural transition points obtained in the present study agree with those reported by Subramanian, Kini, Dec and Sloan [1].…”
Section: Resultssupporting
confidence: 71%
“…This experimental setup and procedure employed to measure phase equilibrium with the Titanium pressure cell was validated by measuring HVLE data of pure CH4 and pure H2O. A p-T dissociation point of (9.459 MPa, 285.79 K) is measured, which is in good agreement with the average value of (9.441 MPa, 285.74 K) from other experiments [50][51][52][53].…”
Section: Methodssupporting
confidence: 71%
“…For most other gas hydrates, which exist at pressures much lower than that of methane hydrate, the method outlined here is also expected to work extremely well. [20] 19.06 Roberts et al [21] 54.36 Deaton and Frost [6] 55.12 McLeod and Campbell [14] 55.07 Marshall et al [10] 53.41 Yoon et al [22] 53.81 17.53 Glew [23] 55.36 18.06 Present work 52.9 ± 1.3 17.47 ± 0.10 In evaluating the fugacity it is assumed that the gas is pure methane, whose equation of state is found in the NIST webbook [9]. The methane solubility found by the procedure outlined above is given in figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…The volume change for reaction (1a) is Galloway et al [12] Deaton and Frost [6] Kobayashi and Katz [13] McLeod and Campbell [14] Verma [15] de Roo et al [16] Thakore and Holder [17] Adisasmito et al [18] Makogon and Sloan [7] DV 1a ¼ 1 À…”
Section: Finding Dv(tp)mentioning
confidence: 99%